2007
DOI: 10.1161/01.res.0000252828.17939.00
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Ryanodine Receptor Open Probability Alone Does Not Produce Arrhythmogenic Calcium Waves

Abstract: Abstract-Diastolic waves of Ca 2ϩ release have been shown to activate delayed afterdepolarizations as well as some cardiac arrhythmias. The aim of this study was to investigate whether increasing ryanodine receptor open probability alone or in the presence of ␤-adrenergic stimulation produces diastolic Ca release from the sarcoplasmic reticulum (SR). When voltage-clamped rat ventricular myocytes were exposed to caffeine (0.5 to 1.0 mmol), diastolic Ca 2ϩ release was seen to accompany the first few stimuli but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
151
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(166 citation statements)
references
References 44 publications
14
151
1
Order By: Relevance
“…Consistent with previous reports, cell capacitance was significantly lower in atrophic than in control cardiac myocytes (123±3 pF, n=96 vs. 161±5 pF, n=98, p<0.0001) [40]. At a holding potential of V Pip =−90 mV, Ca 2+ release from the SR was induced by rapid superperfusion of the investigated cardiac myocyte with 10 mmol/l caffeine [30,38,49,50,54]. In the presence of caffeine, Ca 2+ is released from the SR, cannot be stored in the SR again and is therefore completely removed from the cytoplasm by the Na + -Ca 2+ exchanger [8,27].…”
Section: Sr Ca 2+ Contentsupporting
confidence: 91%
“…Consistent with previous reports, cell capacitance was significantly lower in atrophic than in control cardiac myocytes (123±3 pF, n=96 vs. 161±5 pF, n=98, p<0.0001) [40]. At a holding potential of V Pip =−90 mV, Ca 2+ release from the SR was induced by rapid superperfusion of the investigated cardiac myocyte with 10 mmol/l caffeine [30,38,49,50,54]. In the presence of caffeine, Ca 2+ is released from the SR, cannot be stored in the SR again and is therefore completely removed from the cytoplasm by the Na + -Ca 2+ exchanger [8,27].…”
Section: Sr Ca 2+ Contentsupporting
confidence: 91%
“…Another stimulus is, therefore, needed to keep sarcoplasmic reticulum Ca 2+ content at a level sufficient for Ca 2+ wave production. 47 We believe that in ADHF, continued βAR stimulation activates CaMKII, causing diastolic Ca 2+ leak from the sarcoplasmic reticulum via ryanodine receptor phosphorylation, and that PKA activation maintains sarcoplasmic reticulum Ca 2+ at a level sufficiently high for the production of arrhythmogenic Ca 2+ waves. In addition to alterations in Ca 2+ handling, CaMKII can also phosphorylate ion channels.…”
Section: Calcium/calmodulin-dependent Protein Kinase IImentioning
confidence: 98%
“…14 This increased opening will lead to a diastolic leak of Ca, thereby decreasing the SR Ca content. In addition to decreasing systolic function, the leak may also interfere with relaxation by opposing Ca reuptake into the SR. 15 The relative importance of decreased SERCA activity as opposed to increased NCX and RyR leak may depend on the exact model used. For example, in a canine model of heart failure induced by rapid pacing, 16 it was found that the bulk of the problems of Ca handling could be attributed to increased leak, whereas in a rabbit model, aortic insufficiency and stenosis changes of NCX were most important.…”
Section: Sr Function In Heart Failurementioning
confidence: 99%